DETECTION AND IDENTIFICATION OF YELLOW MOSAIC STUNT DISEASE ON Petunia sp. USING NESTED PCR METHOD - Astuti, Suryani Titi; Sulandari, Sri; Hartono, Sedyo; Somowiyarjo, Susamto (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Detection and identification of yellow mosaic stunt disease on Petunia sp. using nested PCR method. Yellow mosaic stuntdisease was found at some nurseries of Petunia in Sleman, Yogyakarta, also in Muntilan and Magelang Central Java. Thedisease was very important due to its ability reducing the quality and quantity of Petunia seedlings. The causal agent of thedisease may be carried over to imported seeds and necessary to identify as a basic information for developing controlstrategies. This research was done by mechanical transmission on indicator plants. The observation of the causal agents wasconducted using electron microscope with quick dipping method and the molecular detection was done using nested PCRwith TobRT up1-TobRT do2 as the external primers and TobN up3-TobN do4 as the internal primers. Mechanical inoculationshowed chlorosis symptoms that developed into local spot on Chenopodium amaranticolor as well as mosaic and veinbanding on Nicotiana benthamiana. The observation using electron microscope showed rod-shaped virus particles sizedapproximately 300 nm and by PCR method produced around 568 bp and 400 bp DNA band. Based on the sequence analysis,the disease was caused by Rehmania mosaic virus. This type of Tobamovirus has 96% similarity with ReMV-Japan. ReMV, aplant pathogen which was a member of Tobamovirus that has never been reported in Indonesia. This research was the firstreport of ReMV in Indonesia infecting Petunia as ornamental plant.